Optimising The Implementation of Building Information Modelling in 4D (Scheduling) and 5D (Cost) for Highway and Bridge Construction - Kassim, AG.S.A.AG; Sarman, A.M. (International Journal of Integrated Engineering, 2025)
Building Information Modelling (BIM) is a shared knowledge repository for information about a facility that serves as a trustworthy foundation for decision-making throughout the facility's life cycle, which is described as "existing from inception to demise." BIM is still lacking in usage and awareness of BIM benefits in implementation in the highway and bridges construction industry. Furthermore, the disconnect between project scheduling, cost estimation, and BIM models exacerbates the complexity of construction processes, hindering the seamless integration of BIM in highway and bridge projects. Therefore, the objective of this study is to identify the current level of awareness of Building Information Modelling implementation in the highway and bridge construction industry, to produce a BIM 4D (Scheduling) and 5D (Cost Estimating) model based on the highway and bridge construction project and to recognize the benefits and challenges of implementing Building Information Modelling approaches in the highway and bridge construction industry. This research conducted an industrial survey, literature review, and 4D/5D BIM modelling focusing on the Malaysian highway and bridge construction industry. The results suggest that the industry has a moderate understanding of 4D/5D BIM but has superior scheduling and cost estimating skills. The three highest listed benefits are improved on-site cooperation, model-based cost estimation, and project visualization in preconstruction with 3.633, 3.767 and 3.900 mean rank respectively. The three highest-ranked challenges are technical problems, legal challenges, and reluctance to change with 3.500, 3.467 and 3.400 mean rank respectively. In order to replicate the 4D/5D model, modelling is constructed using Infraworks, MS Project, and Navisworks.